Older persons' experiences of adapting to daily life at home after hospital discharge: a qualitative metasummary - Christine Hillestad Hestevik; Marianne Molin; Jonas Debesay; Astrid Bergland; Asta Bye (BMC, 2019)
Abstract Background Researchers have shown that hospitalisation can decrease older persons' ability to manage life at home after hospital discharge. Inadequate practices of discharge can be associated with adverse outcomes and an increased risk of readmission. This review systematically summarises qualitative findings portraying older persons' experiences adapting to daily life at home after hospital discharge. Methods A metasummary of qualitative findings using Sandelowski and Barroso's method. Data from 13 studies are included, following specific selection criteria, and categorised into four main themes. Results Four main themes emerged from the material: (1) Experiencing an insecure and unsafe transition, (2) settling into a new situation at home, (3) what would I do without my informal caregiver? and (4) experience of a paternalistic medical model. Conclusions The results emphasise the importance of assessment and planning, information and education, preparation of the home environment, the involvement of the older person and caregivers and supporting self-management in the discharge and follow-up care processes at home. Better communication between older persons, hospital providers and home care providers is needed to improve the coordination of care and facilitate recovery at home. The organisational structure may need to be redefined and reorganised to secure continuity of care and the wellbeing of older persons in transitional care situations.